Effect of heat shock on the mutagenicity of mutagens and carcinogens in Euglena gracilis - Chreno, O; Krajcovic, J; Ebringer, L; Polónyi, J (Teratogenesis, carcinogenesis, and mutagenesis, 1988)
The effect of heat-shock treatment (42 degrees C for 15 min) on the ability of four mutagens and carcinogens to induce hereditary bleaching in Euglena gracilis cells was investigated. All four mutagens (treatment time: 1-24 h) tested after heat shock increased the frequency of bleached mutants of Euglena gracilis.
Keywords: vysoká teplota; elektronová mikroskopie; Euglena gracilis; mutageny; Mutation; mutace; Animals; Hot Temperature; Mutagenicity Tests; Carcinogens; Mutagens; karcinogeny; zvířata; Microscopy, Electron; testy genotoxicity